Factors Which Will Affect The Business Risk Clients, Audit Risk, Business Risk Auditor, And Auditor’s Competency In Client Selection: Study On Auditor At KAP In Medan - M. Faisal Rizky HSB (TRIGIN PUBLISHER, 2021)
This Study aims to examine how far the influence of business research client, audit risk, business research auditor, auditor's competency to client selection either partial or simultaneous. Hypothesis of this study are business research client, audit risk, business research auditor, auditor's competency influence to client selection either partial or simultaneous. The method of collecting data is done through a questionary that share to Auditor whom work in audit firm. This study uses associative causal with multiple linear regression and also for examine hypothesis uses F test (simultaneous test) and t test (partial test). Results of this study interprets to indicate that business rist client, audit risk, business rist auditor, auditor's competency has influence to clients selection simutaneously and from result of examine t test indicate that audit risk.